2019
DOI: 10.1101/655225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulatory regions in natural transposable element insertions drive interindividual differences in response to immune challenges in Drosophila

Abstract: Variation in gene expression underlies inter-individual variability in immune response.However, the mutations responsible for gene expression changes remain largely unknown. In this work, we searched for transposable element insertions present at high population frequencies and located nearby immune-related genes in Drosophila melanogaster. We identified 12 insertions associated with allele-specific expression changes in immune-related genes. We showed that transgenically induced expression changes in most of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 191 publications
(238 reference statements)
2
13
0
Order By: Relevance
“…We chose 11 TEs with at least one additional line of evidence to perform in vivo enhancer reporter assays (Table 4). We also included in Table 4 three TEs, tdn8 ( transpac ), FBti0020057 ( BS ) and FBti0018868 ( 297 ), which were previously tested in our laboratory (44). All these TEs contained three or more TFBMs/TFBSs, except FBti0019453 ( jockey ) that contained two and FBti0020057 ( BS ) that contained one (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose 11 TEs with at least one additional line of evidence to perform in vivo enhancer reporter assays (Table 4). We also included in Table 4 three TEs, tdn8 ( transpac ), FBti0020057 ( BS ) and FBti0018868 ( 297 ), which were previously tested in our laboratory (44). All these TEs contained three or more TFBMs/TFBSs, except FBti0019453 ( jockey ) that contained two and FBti0020057 ( BS ) that contained one (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Experimental design indicates the region that was cloned in front of the reporter gene. We also included the data for three reporter assays performed previously in the lab (44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of mutations might differ in the complexity of their molecular and fitness-related effects, as has been suggested for transposable element (TE) induced mutations (9)(10)(11). TEs can affect gene structure and gene expression through many different molecular mechanisms (11,12), and some of these changes have been associated with adaptive phenotypes (13)(14)(15)(16)(17)(18)(19). In Drosophila, a dual role as enhancer and promoter of an adaptive insertion conferring tolerance to bacterial infection has been recently reported (19).…”
Section: Introductionmentioning
confidence: 99%
“…TEs have also been frequently associated with insecticide-resistance in Drosophila species (Carareto et al 2014; Rostant et al 2012; Mateo et al 2014). In addition, population genetics studies suggested that more than 84 TE copies in D. melanogaster may play a positive role in fitness-related traits (Rech et al 2019), including xenobiotic resistance (Mateo et al 2014) and immune response to Gram-negative bacteria (Ullastres et al 2019).…”
Section: Introductionmentioning
confidence: 99%